The Integration of Verbal Humor into EFL Classrooms: The Issues of Appropriateness and Relevance in Focus - Minoo Alemi; Hessameddin Ghanbar; Atefeh Rezanejad (National Research University Higher School of Economics, 2021)
The present study examined the manifestations of Iranian male and female EFL teachers' use of humor in the classroom environment. To this end, a qualitative study with 30 participants was implemented in two English language institutes in Iran. Equally, 15 male and female EFL teachers were selected by convenience sampling and their classes were audio-recorded and later transcribed for the examination of the types of humor they used and their frequency. Wanzer, Frymier, Wojtaszcyk, and Smith's (2006) method of humor analysis and categorization of appropriateness was exploited for the analysis of the types of humor collected from the participants of the study. The results suggested that the use of humor by male teachers was more frequent than that of female teachers. It was revealed that 57% of the humor production was by male EFL teachers and 43% was produced by female EFL teachers. The results revealed that the most frequent humor type in male teachers' classrooms was "funny comments" (27%), with "teasing students" (3%) being the least frequent one. In the case of appropriate humor use, similarly, female teachers used "funny comments" (52%) as the most frequent one, while there was no instance of "providing humorous examples". Considering inappropriate humor use, both male and female teachers used "funny comments" (45%) as the most frequent type. The findings of the present study can be of use to EFL teachers and suggests the need for workshops and training courses on the integration of humor into EFL classes.